Maturation of the lower oesophageal sphincter in the preterm baby. - Newell, S J (1988)
There are few reported studies of the lower oesophageal sphincter in preterm infants and none has investigated babies of less than 34 weeks gestation. Using a modified manometric technique suitable for use on very low birth weight infants we have measured sphincter pressures on 68 occasions in 25 infants of postconceptional age between 27 and 41 weeks. In even the most preterm infants the lower oesophageal sphincter could be defined. The mean effective sphincter pressure rose from 3.8 mmHg in infants of less than 29 weeks gestation to 18.1 mmHg in the term infant. This rise in effective sphincter pressure correlated well with increasing postconceptional age (r = 0.81). This pattern of maturation in our patients was unaffected by intrauterine growth retardation, postnatal illness, or concurrent xanthine administration.